146k views
4 votes
2. For each expression, write an equivalent expression by applyingthe distributive property.a. (x+2)(x+ 9)b. (x + 4)(2x - 1)c. (x - 5)

User Carlos
by
4.8k points

1 Answer

2 votes

Accoding to the distributive property,


(a+b)\ast(c+d)=a\ast(c+d)+b\ast(c+d)

a.

Apply the property to the given expression,


\begin{gathered} (x+2)(x+9) \\ =x\mleft(x+9\mright)+2\mleft(x+9\mright) \\ =x^2+9x+2x+18 \\ =x^2+11x+18 \end{gathered}

Thus, the given equivalent expression is,


x^2+11x+18

b.

Apply the property to the given expression,


\begin{gathered} (x+4)(2x-1) \\ =x(2x-1)+2(2x-1) \\ =2x^2-x+4x-2 \\ =2x^2+3x-2 \end{gathered}

Thus, the given equivalent expression is,


2x^2+3x+2

c.

To apply the Distributive Property, we need a 3rd term. But here are only two terms in the expression.

So the only other possible way to write the equation using Distributive property is given as,


\begin{gathered} (x-5) \\ =1(x-5) \\ =1(x)-1(5) \end{gathered}

Thus, the required equivalent expression is ,


1(x)-1(5)

User Pradeexsu
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.